Satisfaction with the work of nurses - Joković Sandra; Kekuš Divna; Despotović Mile; Pavlović Jelena; Hadživuković Natalija (Association of Nurses Technicians and Midwives, 2018)
Introduction. Satisfaction with work and experiencing positive emotions at work is considered to be an important part of nursing professional life, and has a significant impact on patient safety, the quality of services provided, commitment and stay in the organization and profession. The aim of this paper was to examine the level of satisfaction with the work of nurses. Material and methods. The research is designed according to the type of cross section study. The research sample consisted of 200 nurses working at the University Hospital Foča, the Health Center Zvornik and the Health Center Istočno Sarajevo. The instruments used in this in research are: sociodemographic questionnaire and the Job Satisfaction Survey (JSS). Statistical analysis of data was made using the SPSS software statistical package. Of the statistical tests was used χ2-square test. As a level of statistical significance, the difference was taken as the usual value of p <0.05. Results. Statistically significant negative correlation was established between satisfaction with the work and socio-demographic characteristics of the respondents (r = -0,252; p = 0,017). The prospects for improvement are satisfied with 25% of the respondents, 37% had an ambivalent attitude, while 38% of respondents expressed dissatisfaction. Twenty-three percent of respondents are satisfied with communication in the organization of work, 35% are ambivalent, while 42% of respondents are dissatisfied. 21% of the respondents expressed satisfaction with the benefits and on the rewards for a well-done job, 45% were ambivalent, while 34% of the respondents were dissatisfied. Conclusion. The lowest ratings of our respondents in wage domains, rewards for well-designed work and working conditions are probably the result of the economic climate in which lives and works, fixed and inadequate wages and minimum benefits combined with the nature of the work.